PENGARUH PENGALAMAN PRAKTEK KERJA INDUSTRI (PRAKERIN) DAN HASIL UJIAN KOMPETENSI KEAHLIAN TERHADAP KESIAPAN SISWA MEMASUKI DUNIA KERJA SISWA KELAS XII KOMPETENSI KEAHLIAN AKUNTANSI SMK KOTA SOLOK - Angra Melina; Yerizon Dr (Jurnal Kajian Pendidikan Ekonomi, 2015)
This research is purposed to reveal(1) The effect of Prakerin experience to readiness to enter workforce (2)The effect of Prakerin experience to result of vocational competence examination(3) The effect of Prakerin experience and result of vocational competence examination to readiness to enter workforce.Research did in XIIclass major accountingin SMK Solok City, SMK 1 Solok and SMK Kosgoro, at May – July 2014. Type of research is descriptive causative. The study population is 111 numbered. Research sample used proportional random sampling. The samples taken were 87 student. Collecting data using questionnaires and documentation.Processing using path analyze. Therefore, there is a conclusionThe effect of Prakerin experience to readiness to enter workforce The effect of Prakerin experience to result of vocational competence examination and effect of Prakerin experiences and result of vocational competence examination  to readiness to workforce. Keyword : experience prakerin, vocational competence test, readiness to enter workforce